Penerapan E-Modul Berbasis Budaya Jawa Untuk Meningkatkan Kemampuan Literasi Numerasi Matematis Siswa Materi Kesebangunan - Alhikma, Riska; Marzuki, Marzuki; Anggreni, Fenny (Jambura Journal of Mathematics Education, 2025)
This study aims to examine the effectiveness of implementing a Javanese culture-based e-module on similarity material in improving the mathematical numeracy literacy skills of students at SMP Negeri 1 Lima Puluh Pesisir. The study employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The population consisted of all seventh-grade students of SMP Negeri 1 Lima Puluh Pesisir in the 2024/2025 academic year. The sample comprised 30 students from class VII-2 selected through systematic sampling. The research instrument was a mathematical numeracy literacy test developed based on similarity indicators and validated by experts, followed by validity and reliability testing. The data were analyzed using descriptive and inferential statistics through a paired sample t-test. The results showed that the students’ mean scores increased from 59.53 in the pretest to 71.63 in the posttest, with an N-Gain value of 0.30, which falls into the moderate category. The paired sample t-test results indicated a statistically significant difference between the pretest and posttest scores (p 0.05). These findings indicate that the Javanese culture-based e-module is effective in improving students’ mathematical numeracy literacy skills on similarity material while simultaneously fostering local cultural values. This learning innovation aligns with the principles of the Merdeka Curriculum, which emphasizes contextual learning and culture-based character development.